Increased Microleakage of Amalgam Restorations after Exposure to 2.4 Ghz Radiofrequency Electromagnetic Fields from Common Wi-Fi Routers - Mortazavi SMJ; Dehghani Nazhvani A; Shahidi Sh; Haghani M; Paknahad M (Shiraz University of Medical Sciences, 2017)
Statement of Problem: Previous studies have shown that exposure of dental amalgam fillings to MRI and mobile phones can increase microleakage of amalgam restorations. Objectives: The aim of this study was to evaluate the effects of exposure to radiofrequency radiation emitted from indoor Wi-Fi access devices on microleakage of amalgam restorations. Materials and Methods: Standard class V cavities were prepared on the buccal surfaces of 69 extracted human premolar teeth. The samples were divided into two exposure groups and one non-exposed control group of 23 teeth each. The specimens in the experimental groups were exposed to a radiofrequency (RF) radiation emitted from a commercial 2.4 GHz Wi Fi router. The distance between the Wi-Fi router and samples was 30 cm and the router was exchanging data with a laptop computer that was placed 20 m away from the router. Teeth samples in the first exposure group (group A) were exposed to RF for 3 days while the second exposure group (group B) was exposed for 6 days. Then the teeth were sectioned and scored for microleakage under a stereomicroscope. Results: The score of microleakage was significantly higher in the exposure group A compared to that of the control group. However, the score of microleakage was not significantly different between the exposure group B and control group. Furthermore, the scores of microleakage was signifi-cantly higher in the exposure group A than that of the exposure group B. Conclusions: Exposure of patients with amalgam restorations to radiofre-quency waves emitted from commercial Wi-Fi routers can lead to in-creased microleakage of amalgam restorations.